The Intra-household Division of Labor – An Empirical Analysis of Spousal Influences on Individual Time Allocation - Julia Bredtmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Regarding total working hours, including both paid and unpaid labor, hardly any differences between German men and women exist. However, whereas men allocate most of their time to market work, women still do most of the non-market work. Using the German Time Use Surveys 1991/92 and 2001/02, this paper aims to analyze the interactions between the time use decisions of partners within one household. Thereby, an interdependent model of the partners' times allocated to paid and unpaid work that allows for simultaneity and endogeneity of the time allocation decisions of the spouses is applied. The results suggest that male time in market and non-market work is unaffected by their wife's time use, while women adjust their time allocation to the time schedule of their partner. These findings might partly explain why in Germany - and other European countries as well - gender differences in employment and wages still persist. – – Die Studie untersucht die Arbeitsteilung von Paaren innerhalb eines Haushalts. Unter Verwendung von Zeitbudgeterhebungsdaten der Jahre 1991/92 und 2001/02 wird der Einfluss der Zeiteinteilung zwischen bezahlter und unbezahlter Arbeit des einen Partners auf die Zeitallokation des anderen Partners untersucht. Die Zeitallokationsentscheidungen der Partner werden dabei unter Verwendung eines interdependenten Modells geschätzt, das die Simultanität und Endogenität der Entscheidungen berücksichtigt. Die Ergebnisse zeigen deutliche Unterschiede hinsichtlich des Einflusses der Zeitverwendung des Partners zwischen Männern und Frauen. Während das Arbeitsangebot von Männern unabhängig von der Zeitallokation der Partnerin ist, passen Frauen ihr Arbeitsangebot an das ihres Partners an.
Keywords: J16; J22; C34; 330; intra-household division of labor; time allocation; structural equation model